2000
DOI: 10.1038/35024064
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical evidence of cannibalism at a prehistoric Puebloan site in southwestern Colorado

Abstract: The existence of cannibalism is one of the most controversial issues in the archaeology of the American Southwest. Disarticulated, cut-marked and heat-altered human remains from non-burial contexts at prehistoric Puebloan (Anasazi) archaeological sites in the Four Corners region of the American Southwest have been interpreted by some scholars as evidence of cannibalism. Osteological studies indicate that many of the disarticulated bodies found at these sites were processed in a manner consistent with food prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(36 citation statements)
references
References 11 publications
1
32
0
3
Order By: Relevance
“…The importance in identifying human origin was brought to the forefront in analyses of purported cannibal coprolites Dongoske et al, 2000;Lambert et al, 2000;Marlar et al, 2000). This is especially true in this study because we present the facts that animal bone, hair, and intestinal residue were found in human coprolites.…”
Section: Methodological Considerations: Dust Devil and Hinds Cavesmentioning
confidence: 57%
“…The importance in identifying human origin was brought to the forefront in analyses of purported cannibal coprolites Dongoske et al, 2000;Lambert et al, 2000;Marlar et al, 2000). This is especially true in this study because we present the facts that animal bone, hair, and intestinal residue were found in human coprolites.…”
Section: Methodological Considerations: Dust Devil and Hinds Cavesmentioning
confidence: 57%
“…Although skeletal remains obviously have advantages, for example, for the study of social contexts revealed by burial practices, these findings show that paleofeces from dry cave and rock shelter sites represent a source of ancient DNA that is relatively abundant, and from which the DNA is more reliably retrievable than is the case for human skeletal remains. In addition, paleofecal DNA offers valuable information on the meat and plant components of ancient diets that complements and extends information obtainable by morphological and biochemical (26) analyses. Finally, paleofeces may be more accessible to scientific study than other remains, because they do not represent objects of spiritual value (27).…”
Section: Discussionmentioning
confidence: 99%
“…Aunque existen otras formas de detección de las prácticas caníbales, como los estudios de mioglobina en heces, tal y como se ha documentado en los indios navajo (Marlar et al, 2000), o los hallazgos de proteínas priónicas asociadas a los kuru en el caso de Papúa (Collinge et al, 2008), estas no se han aplicado aún con éxito a cronologías prehistóricas.…”
Section: Métodosunclassified